TEACHING TRANSLATION STRATEGIES OF ENGLISH NEWS ARTICLES - Eshboyev Abdushukur Berdinazarovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The increasing globalization of media necessitates effective translation of English news articles into other languages. News translation is distinct from general translation, requiring specialized strategies that address linguistic, cultural, and journalistic aspects. This scientific research explores teaching methodologies for translation strategies specific to English news articles. By analyzing the features of news language, identifying challenges, and proposing pedagogical solutions, this work provides a comprehensive framework for educators. Using qualitative and quantitative research methods, the study evaluates the effectiveness of various teaching strategies, emphasizing hands-on practice, cultural sensitivity, and technological integration. The global demand for effective news translation underscores the importance of developing specialized strategies for translating English news articles. This article examines the linguistic, cultural, and journalistic features of English news articles and their implications for translation education. It proposes an integrated pedagogical framework combiing theoretical instruction, hands-on practice, cultural sensitivity, and technological tools to train aspiring translators. The study highlights key challenges, including lexical ambiguity, cultural adaptation, and journalistic ethics, while offering practical solutions for educators.